A measuring complex for control the uniformity of the light output of scintillators - Tretyak, S.O.; Popkova, O.V. (Functional Materials, 2018)
A complex was developed and manufactured for monitoring the uniformity of the light output of ZnSe scintillators when excited by X-ray radiation, suitable for servicing mass production of scintillation elements and investigating the distribution of light output over the surface of scintillators.